Ureteroscopy-assisted retrograde nephrostomy for lower calyx calculi in horseshoe kidney: two case reports - Kawahara Takashi; Ito Hiroki; Terao Hideyuki; Tanaka Katsuyuki; Ogawa Takehiko; Uemura Hiroji; Kubota Yoshinobu; Matsuzaki Junichi (Journal of Medical Case Reports, 2012)
Abstract Introduction We previously reported on the effectiveness of ureteroscopy-assisted retrograde nephrostomy during percutaneous nephrolithotomy and report two cases of lower calyx calculi in horseshoe kidney that were successfully treated with ureteroscopy-assisted retrograde nephrostomy. During the ureteroscopy-assisted retrograde nephrostomy procedure, a ureteroscope is advanced in the desired calyx and a Lawson retrograde nephrostomy puncture wire is inserted. The wire is advanced through the calyx to exit the skin. The wire is then used for the percutaneous dilation. Case presentation Case 1 was a 68-year-old man who was shown on radiography to have left lower calyx calculi (19 × 15mm, 7 × 5mm, and 7 × 3mm) in horseshoe kidney. Case 2 was a 36-year-old woman shown on radiography to have a left lower calyx calculus (10 × 8mm) in horseshoe kidney. Conclusions Both patients were stone-free after ureteroscopy-assisted retrograde nephrostomy during percutaneous nephrolithotomy. Ureteroscopy-assisted retrograde nephrostomy is a promising procedure for safely and effectively treating lower calyx stones in horseshoe kidney.